Data-driven process discovery and analysis 8th IFIP WG 2. 6 International Symposium, SIMPDA 2018, Seville, Spain, December 13-14, 2018, and 9th International Symposium, SIMPDA 2019, Bled, Slovenia, September 8, 2019, Revised selected papers /: 8th IFIP WG 2. 6 International Symposium, SIMPDA 2018, Seville, Spain, December 13-14, 2018, and 9th International Symposium, SIMPDA 2019, Bled, Slovenia, September 8, 2019, Revised selected papers. (2020) - Unknown
No abstract available